PENGARUH SUHU DAN JANGKA WAKTU PENGERINGAN WORTEL TERHADAP BEBERAPA KARAKTERISTIK TEPUNG WORTEL - Kelik Putranto (Ma'soem University, 2021)
The carrot has a sweet flavor and is one of the most popular versatile root vegetables. Carrot powder should be produced from carrot roots without damaging its carotene. The product may be moxed to many foods especially baby foods. The manufacturing procedure is relatively easy, simple and inexpensive. In manufacturing process of carrot powder, temperature and time of drying should be properly adjusted. The experiment was conducted in the laboratory of Chemistry and Food Processing, Faculty of Agriculture, Ma'soem University in June 2021. The experiment used a Split Plot Design with Randomized Block as the basic design. It was consisted of two factors having both three levels and three replications. The first factor was drying temperature i.e 550C, 600C and 650C. The second factor was drying time i.e 17 hours, 20 hours and 23 hours. The examined parameters were moisture, vitamin C, reduction sugars, and crude fibers contents and also organoleptic color, aroma and texture. It can be concluded that: there was an interactions effect between temperature and time of drying on moisture and vitamin C contents of produced carrot powder. The 650C of drying gave the best characteristic of carrot powder based on color, aroma, texture and crude fibers. The 23 hours of drying time gave the best characteristic of carrot powder based on colors, aroma, texture, reduction sugars and crude fibers.